1959
DOI: 10.1002/cber.19590920930
|View full text |Cite
|
Sign up to set email alerts
|

Über bi‐ und polycyclische Azulene, XL. Azulenglyoxylsäuren und Azulencarbonsäuren, ihre Darstellung und Reduktion mit Lithiumalanat

Abstract: Azulen-l(bzw. 3)-glyoxylsriuren und -carbons&mn w d e n aus Azulenen undOxalylbromid ohne Katalysatoren dargestellt. Die Reduktion von Azulenmonocarbonsiiuren, -glyoxyls%uren und -dicarbonsiluren wurde untersucht. Die optischen Eigenschaften der erhaltenen Azulenderivate werden diskutiert. A. DIE CARBOBROMlERUNG VON AZULENEN (mit HARRY ORITMA")Wie in einer KurPnitteilung2) angegeben, konnen be-i der Einwirkung von Oxalylbromid auf geeignete organische Verbindungen ohne Zusatz von Katalysatoren, je nach der Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…A combination of 1 H- and 13 C-NMR, HMQC, and HMBC experiments determined the structure of this compound as 2,2‘-diguaiazulenylmethane. A literature survey revealed that 2 was originally reported as a synthetic product. , Later, the same compound was isolated from the deep-sea gorgonian Pseudothesia sp . Spectral data of 2 were identical to those reported for this compound.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…A combination of 1 H- and 13 C-NMR, HMQC, and HMBC experiments determined the structure of this compound as 2,2‘-diguaiazulenylmethane. A literature survey revealed that 2 was originally reported as a synthetic product. , Later, the same compound was isolated from the deep-sea gorgonian Pseudothesia sp . Spectral data of 2 were identical to those reported for this compound.…”
supporting
confidence: 55%
“…Spectral data of 2 were identical to those reported for this compound. The structure of 2 was further confirmed by chemical transformation of guaiazulene following the method developed by Treibs …”
mentioning
confidence: 99%
“…Oxalyl bromide could be equally used as a glyoxylating agent [ 49 50 ]. Likewise, the glyoxylation of 1b has been reported to proceed in 3-position with both reagents, yet with lower reactivity, and its conversion was found to be incomplete even after 2 h. In addition, the formation of side products [ 51 ] and decarbonylation [ 52 ] was observed, presumably caused by the steric hindrance of the methyl group in 4-position.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available guaiazulene (1) was used as starting material for the synthesis of 3a-e, via the intermediate 3-acyl bromide 2 [12], according to the procedure of Treibs [11]. The presence of an electron withdrawing group rendered the p-bromobenzyl ester 3e labile, and aminolysis with benzylamine in refluxing toluene led smoothly to the corresponding amide 3f.…”
Section: Chemistrymentioning
confidence: 99%
“…As a part of our ongoing program concerning the use of phytochemicals as starting materials for the synthesis of compounds with potential biological activities, our research interest was stimulated by earlier research work on the one-pot preparation of various 3-guaiazulene carboxylates [11]. We present herein the efficient introduction of various C-3 functionalities on the azulene skeleton of this readily available, non-toxic natural product and evaluation of the biological properties of the compounds thus prepared.…”
Section: Introductionmentioning
confidence: 99%